Prevalence of Non-Strabismic Binocular Vision Dysfunction in A Hospital based Population (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study was aimed towards finding the prevalence of non strabismic binocular vision dysfunctions(NSBVD) in the Indian population presenting with different symptoms pertaining to binocular visiondisorders. Method: This retrospective study included one hundred and sixty one patients who presentedto the out- patient department with symptoms of binocular vision dysfunction, during a period of oneyear. Patients were in the age group of 18 ±6.93, with 71 males and 90 females. Their binocular visiondysfunction was assessed via several diagnostic modules/tools designed for binocular vision assessment.Results: Results indicate that the most common binocular vision anomalies in this studied population arefusional vergence dysfunction with accommodative infacility (40.38%), convergence insufficiency withaccommodative infacility (24.36%), Fusional vergence dysfunction (7.05%). Convergence Insufficiencyand Accommodative infacility showed the same prevalence of 7.7%. Discussion: Accommodative and nonstrabismic binocular vision dysfunctions are commonly underdiagnosed/undiagnosed in clinical practice.These disorders affect academic performance, sports activities and general quality of life. An appropriatedetailed orthoptic examination and accurate diagnosis is necessary to manage these binocular visiondysfunctions.